2013
DOI: 10.1016/j.ijrobp.2012.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Dose Escalation for Locally Advanced Lung Cancer Using Adaptive Radiation Therapy With Simultaneous Integrated Volume-Adapted Boost

Abstract: Purpose Test the feasibility of a planned phase I study of image-guided adaptive radiotherapy in locally advanced lung cancer. Methods and Materials Weekly 4D FBCTs of ten lung cancer patients undergoing concurrent radiochemotherapy were used to simulate adaptive radiotherapy: After an initial IMRT plan (0–30 Gy/2 Gy), adaptive replanning was performed on week 2 (30 to 50 Gy/2 Gy) and week 4 scans (50 to 66 Gy/2 Gy) to adjust for volume and shape changes of primary tumors and lymph nodes. Week 2 and 4 clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…9 In another study which adapted at weeks 2 and 4 conducted by Weiss et al, an average increase of 13.4 Gy with a maximum of 23.4 Gy was achieved. 10 These values are larger than those reported here for daily adaptation; differences may be attributed to volumes used to estimate escalation, i.e., in this work, dose was escalated to the CTV as opposed to primary tumor. Furthermore, average primary tumor regression for the synthetic dataset was smaller than those other researchers have observed clinically as previously noted.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…9 In another study which adapted at weeks 2 and 4 conducted by Weiss et al, an average increase of 13.4 Gy with a maximum of 23.4 Gy was achieved. 10 These values are larger than those reported here for daily adaptation; differences may be attributed to volumes used to estimate escalation, i.e., in this work, dose was escalated to the CTV as opposed to primary tumor. Furthermore, average primary tumor regression for the synthetic dataset was smaller than those other researchers have observed clinically as previously noted.…”
Section: Discussionmentioning
confidence: 54%
“…[7][8][9][10] These works implement various replanning schedules ranging from single to weekly adaptations and demonstrate a patient-specific benefit for adaptive plans in the context of tumor regression. While a variety of schedules have been implemented by the respective authors, systematic comparisons between schedules of the varying adaptive frequency have not been performed; furthermore, the nature of tradeoff between the replanning frequency and adaptive benefit is not understood.…”
Section: Introductionmentioning
confidence: 99%
“…With improved RT planning and delivery techniques, it is possible to have the normal lung and heart better spared from radiation, and dose-intensified RT schedules safely administered [69]. It has been found that for patients with locally advanced NSCLC, ART may increase radiation dose to the residual tumor target up to 80 Gy on average, without increasing dose to normal tissue [74,75]. However, more clinical data should be collected to evaluate the impact of ART on normal tissue dose reduction.…”
Section: Prescription For Adaptive Planningmentioning
confidence: 99%
“…It has been reported that plan adaptation performed around fraction 15 and fraction 20 is most diametrically efficient for concurrent and sequential chemoradiotherapy, respectively [79]. Based on iso-toxic Mean Lung Dose (MLD), re-planning twice at weeks 2 and 4 may achieve an average escalation of 13.4 Gy [75], and at weeks 3 and 5 may have an average increase of 7 Gy or a reduction in MLD of approximately 8% [12]. Since tumor shrinkage depends on many factors such as tumor histology, location, stage and imaging modality used in the volume measurement, the optimal time point for plan adaptation and its dosimetric gain could be different for individual patients.…”
Section: Decision For Plan Adaptationmentioning
confidence: 99%
“…The delivered doses can be calculated on a reference image dataset by using deformable dose mapping and accumulation techniques (Mohan et al, 2005, Heath and Seuntjens, 2006). It has been demonstrated that adaptive radiotherapy incorporating deformable dose accumulation (DDA) may facilitate dose escalation and normal tissue sparing (Weiss et al, 2013). Among these techniques, image-intensity-based deformable registration incorporating dose interpolation is a widely used DDA method (Rosu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%